Analisis Faktor – Faktor Pendukung Pelayanan Pendaftaran Pasien Rawat Jalan Di Rumah Sakit Prima Husada Malang - Lilik Afifah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: The registration system at Prima Husada Hospital has used electronics, patients can register online through the website or whatsapp at Prima Husada Malang Hospital. Methods: The research method used is descriptive qualitative, which is a method used by researchers to find knowledge or theories about research at a certain time. research with a qualitative approach using secondary data collection and observation Results: The results of this study indicate that services at the outpatient registration site are in accordance with the standard procedure policies that exist at the registration site at the hospital. In general, facilities at outpatient registration services have met the needs of registration services at the hospital. The officers in carrying out the activities and the cohesiveness given by the head of medical records to co-workers at the registration site are good enough so that the registration activities can take place properly and in accordance with the established procedures. Conclusion:a. The outpatient registration service procedure at Prima Husada Malang Hospital already has a flowchart and requirements for patients.b. Implementation of the Outpatient Registration Procedure at Prima Husada Malang Hospital has been used in accordance with hospital policies.c. Supporting facilities for outpatient registration services at Prima Husada Malang Hospital have covered the needs at the TPPRJ place.d. There are nine human resources officers at the outpatient registration site at Prima Husada Hospital Malang who are at the service station at the registration position so that there is no shortage of manpower and the service runs stably and effectively